La transformation lexicale comme indicateur de l’analyse dans l'enseignement de la traduction du japonais - Gile, Daniel (Meta, 1992)
AbstractLoose lexical usage in Japanese often makes the lack of analysis in a student's translation exercise evident through a word-for-word translation that sounds implausible, illogical, very clumsy or absurd. Lexical processing can therefore often be used as an analysis indicator. The paper illustrates the fact through the example of one Japanese text and its translation. Tabulation enables rapid scrutiny of the situation of each student and of the group as a whole, as well as the assessment of the efficiency of didactic interventions by the instructor. The method cannot be applied as such to all languages, but other indicators, such as the processing of ambiguous or obscure clauses, can be used in a similar way.